Algebraic Bethe Ansatz for the XXZ Gaudin Models with Generic Boundary - Crampe, N. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We solve the XXZ Gaudin model with generic boundary using the modified algebraic Bethe ansatz. The diagonal and triangular cases have been recovered in this general framework. We show that the model for odd or even lengths has two different behaviors. The corresponding Bethe equations are computed for all the cases. For the chain with even length, inhomogeneous Bethe equations are necessary. The higher spin Gaudin models with generic boundary is also treated.